The effect of methanol and some micro-macronutrients foliar application on Maize (Zea mays L.) maternal plant on some quantitative and qualitative characteristics of the seed - E. Khalilvand Behrouzyar; M. Yarnia (علوم و فناوری بذر ایران)
In order to investigate the effect of the foliar application of various combinations on corn maternal plant on some quantitative and qualitative characteristics of the seed an experiment was conducted in factorial form based on RCBD with three replications during growing seasons of 2009-2011. Treatments were four growth stages (the 8-10 leaves, the tasseling, the seed-filling, all the stages), seven levels of foliar application (Methanol, Zn, B, Mg, N, Mn, a mixture of all combinations) and control as a separate plot. The analysis of the data showed a significant effect of the combination type of foliar application in different stages on the reserve of N, protein and starch content and grain yield per plant. The detailed results of the study showed that foliar application with a mixture of all combinations in all stages increased the reserved N and protein content in comparison with control 0/3 and 16 %, respectively. Foliar application with N, Mg, Zn, Mn and B in grain-filling stage, N, Mg and Mn foliar application in tasseling and N, Mg and B foliar application in all stages had the highest germination percent (100%). Therefore, N foliar application in the 8-10 leave, tasseling and the seed-filling stages increased 33% grain yield in comparison with the control.